Find the sum of all real values of x satisfying the equation 3 x + 1 − ∣ 3 x − 1 ∣ = 2 lo g 5 ∣ 6 − x ∣ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
2 cases are needed to be considered 3 x > 1 ⇒ x > 0 and 3 x < 1 ⇒ x < 0
I x > 0 ⇒ 2 = 2 lo g 5 ∣ x − 6 ∣ ⇒ x = 6 ± 5 ⇒ x = 1 , 1 1 II x < 0 ⇒ 2 ∗ 3 x = 2 lo g 5 ∣ 6 − x ∣ ⇒ x=6-5^3^x>1 ⇒ x ∈ ∅ Combining x=1,11......Sum=12
We can break the equation in cases...subsequently 3 cases would be made one for x<=0 then for x<6 and x>6 and as we find x=1 satisfies the equation then by symmetry along x=6 line x=11 would also satisfy..hence 1+11=12
Problem Loading...
Note Loading...
Set Loading...
CaseI : 3 x ≥ 1
3 x + 1 − 3 x + 1 = 2 l o g 5 ∣ 6 − x ∣
1 = l o g 5 ∣ 6 − x ∣
This gives x = 1 , 1 1
CaseII : 3 x ≤ 1
3 x + 1 + 3 x − 1 = 2 l o g 5 ∣ 6 − x ∣
3 x = l o g 5 ∣ 6 − x ∣
Here no solution does not exist since l o g 5 ∣ 6 − x ∣ is always greater than one because l o g 5 6 < l o g 5 ∣ 6 − x ∣ ( s i n c e . . x < 0 ) .
Hence sum of solutions of x is 1 2 .